(3Yde GdfaS hGdGfJGL (B/s - (3GdYjShj, YHO GdQMef eMeOs ((3GdGScfOQjI(B: s (3GdOGQ GdLGeYjI ddWHGYI hGdfTQ hGdJhRjY(B, s, 2000)
(3gPG GdcJGH (B: -1- (3OhQ Yde GdfaS IGdGfJGL (B-2- (3ecGfI Yde GdfaS aj GdUfGYI GdMOjKI (B-3- (3GdfXGe GdQCS eGdj GdeJWQa hYjhHg (B-4- (3ePgH GdMQjI GdaQOjI GdeWdbI (B-5- (3GdUQGY GdUfGYj (B-6- (3GdJhLjg Gdegfj (B-7- (3GdJOQjH Gdegfj (B-8- (3GdebGHdI (B-9- (3bjGS GdYdGbGJ GdELJeGYjI (B-10-(3GdQhM GdeYfhjI (B11- (3JMdjd GdYed (B-12-(3GdXQha GdajRjbjI GdeMjWI HGdYed (B- 13- (3SjchdhLjI GdEOGQI (B-14- (3WHjYI GdSdhc GdEfSGfj (B-15- (3GdOhQ GdSjchdhLj ddeTQa (B-16- (3GdCef GdUfGYj hMhGOK GdYed (B17 (3GdbOQGJ hbjGSgGs
Keywords: (3GfJGL (B- (3Yde GdfaSs